Research on High Robust Multimedia Image Encryption Based on Gyrator Transform Domain Model - Xiaojing Cheng (Advances in Multimedia)
The encryption and privacy protection of multimedia image resources are of great value in the information age. The utilization of the gyrator transform domain model in multimedia image encryption can select parameters more accurately, so it has a wider scope of utilization and further ameliorates the stability of the whole system. On account of this, this paper first analyzes the concept and connotation of gyrator transform, then studies the image encryption algorithm on account of gyrator transform, and verifies the robustness of the gyrator transform algorithm under the influence of noise interference, shear attack, and other factors through the high robust multimedia image encryption and result analysis of gyrator transform.